STRATEGI PRODUK, HARGA, PROMOSI, DAN KEAMANAN TERHADAP PENGAMBILAN KEPUTUSAN MASYARAKAT DALAM MEMILIH BLIBLI.COM SEBAGAI PASAR ONLINE DI JAKARTA - I Made Adnyana (Universitas Nasional, 2020)
This study aims to determine whether there is an influence of product strategy, price, promotion, and security on community decision making in choosing blibli.com as an online / e-commerce market in Jakarta. Research using primary data collected through google doc which contains questionnaires with the unit of analysis studied are people in the DKI Jakarta area. This study was tested using a survey method of research samples as many as 200 people who have accessed and shop at the shopping site Blibli.com. The test equipment used in this study is to use a prerequisite test which includes; normality test, construct validity and reliability test, confirmatory analysis and feasibility test of the overall goodness of fit index. Data analysis method used is Structural Equation Model (SEM) which is assisted with AMOS version 22.0 software. The results of this study indicate that product strategy variables have a positive and real effect on community decision-making in choosing blibli.com as an online / e-commerce market in Jakarta as indicated by the CR value of -2.085> 1.96 and a probability value of 0.037 <0.05 , the price variable has a positive and real effect on community decision making in choosing blibli.com as an online / e-commerce market in Jakarta as indicated by the CR value of 2.104> 1.96 and a probability value of 0.035 <0.05, the promotion variable has a positive effect and real to community decision making in choosing blibli.com as an online / e-commerce market in Jakarta as indicated by the CR value of 2.411> 1.96 and a probability value of 0.016 <0.05, the security variable does not have a positive and real effect on community decision making in choosing blibli.com as an online / e-commerce market in Jakarta as indicated by the CR s value is 1.547 <1.96 and the probability value is 0.122> 0.05